Variation in body temperature of goats and hairy sheep in Sobral, Brazil - Arruda, Francisco de Assis V.; Figueiredo, Élsio A.P.; Pant, Kant P. (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was conducted on breeds of goats and woolless sheep in the tropical northeast Brazil to measure their body temperatures in the morning (at 7:00A.M.) and in the afternoon (at 2:00 P.M.) after exposure to direct solar radiation under simulated conditions of normal grazing. In general there were no marked differences between species of sheep and goats. Significant differences (P<0.05) were observed between breeds when body temperatures were averaged separately for morning and afternoon. The maximum rise in body temperature at 2:00 P.M. was observed in Canindé goats and Santa Inés sheep and relatively minor increases were observed in Bhuj and Anglo-Nubian goats and Morada Nova sheep; minor increases were considered as indices of better adaptability. The overall periodic variations at 2:00 P.M. in body temperatures were closely associated with the fluctuations in the afternoon environmental temperatures.